2011
DOI: 10.1093/brain/awr238
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the seizure onset zone with stereo-electroencephalography

Abstract: Stereo-electroencephalography is used to localize the seizure onset zone and connected neuronal networks in surgical candidates suffering from intractable focal epilepsy. The concept of an epileptogenicity index has been proposed recently to represent the likelihood of various regions being part of the seizure onset zone. It quantifies low-voltage fast activity, the electrophysiological signature of seizure onset usually assessed visually by neurologists. Here, we revisit epileptogenicity in light of neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
183
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(187 citation statements)
references
References 26 publications
3
183
0
1
Order By: Relevance
“…Unlike research in stroke patients, in patients with epilepsy, it is possible to assess the multiple mechanisms of reorganization at different times, including 'chronic' reorganization induced by the epilepsy, 'acute' reorganization induced by surgery, and 'subacute' and 'secondary chronic' reorganization several months or years after surgery. This multimodal approach to evaluate the representation of language is standard for the assessment of language plasticity in epilepsy in our clinical environment (Baciu et al, 2001;Lachaux et al, 2007aLachaux et al, , 2012Jerbi et al, 2010;David et al, 2011David et al, , 2013Vidal et al, 2011;Perrone-Bertolotti et al, 2014). In practice, patients undergo extensive behavioral, neuropsychological, functional, and structural neuroimaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike research in stroke patients, in patients with epilepsy, it is possible to assess the multiple mechanisms of reorganization at different times, including 'chronic' reorganization induced by the epilepsy, 'acute' reorganization induced by surgery, and 'subacute' and 'secondary chronic' reorganization several months or years after surgery. This multimodal approach to evaluate the representation of language is standard for the assessment of language plasticity in epilepsy in our clinical environment (Baciu et al, 2001;Lachaux et al, 2007aLachaux et al, , 2012Jerbi et al, 2010;David et al, 2011David et al, , 2013Vidal et al, 2011;Perrone-Bertolotti et al, 2014). In practice, patients undergo extensive behavioral, neuropsychological, functional, and structural neuroimaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…The grid and strip approach involves a craniotomy and durotomy followed by the placement of two-dimensional strips or sheets (grids) of electrodes (typically 3 mm diameter, 1 cm inter-electrode spacing), where neural activity can be recorded from the surface of the cortex (termed electrocorticography, or ECoG [53][54][55][56][57]). On the other hand, stereoelectroencephalography (SEEG) involves the placement of multi-contact electrode leads penetrating the brain [58][59][60]. While in this review we focus on the grids and strips approach, the principles discussed may be applied to both techniques.…”
Section: (B) Overview Of Cortico-cortical Evoked Potentialsmentioning
confidence: 99%
“…A great number of them have analyzed spectral features of SEEG signals (Bartolomei et al, 2008;David et al, 2011;Gnatkovsky et al, 2011;Gnatkovsky et al, 2014;Andrzejak et al, 2015), which mimic the patterns that are visually identified as epileptogenic during diagnostic EEG inspection (Gnatkovsky et al, 2014;Lagarde et al, 2016). In these works, epileptogenic biomarkers are typically built around two variables, the activation of signal's spectral properties (e.g., the relative amount of signal power in a frequency band (Bartolomei et al, 2008)) and the onset time of this activation, which measure respectively the amount of ictal activity and the degree of early participation of such structures during seizures.…”
Section: Introductionmentioning
confidence: 99%